Schmidt, Eric, Cohen, Jared: The New Digital Age: Reshaping the Future of People, Nations and Business. (Czech Journal of International Relations, 2014)
Schmidt, Eric, Cohen, Jared: The New Digital Age: Reshaping the Future of People, Nations and Business. 1 st ed. New York: Knopf, 2013, 315 stran, ISBN 978-0-307-95713-9.